Notary Authority in Apostille Documents to be Used Abroad Through Apostille: Realizing the Ease of Document Legalization in Border Areas, Especially in Indonesia - Saskia Nabilah; Ferdi; Syofirman Syofyan (Journal of Law, Politic and Humanities, 2024)
The legalization of notary authority in Indonesia is a complex problem, with the issuance of an Apostille certificate to certify the authenticity of the signature, the ability of the person who signed it, as well as the identity of the stamp and seal. This is in line with Article 3 of the Convention on the Elimination of Requirements for the Legalization of Foreign Public Documents or the 1961 Hague Convention (Apostille Convention). The authority of Indonesian notaries to conduct apostille on Notary Deeds used abroad is related to the application of the Apostille Convention. The research used is normative juridical research, focusing on the relationship between the arrangement of apostille on documents used abroad and the application of the Apostille Convention. The authority to issue an apostille certificate depends on the individual country's regulations and the nature of the document. The allocation of authority to grant an Apostille depends on the legal nature of the document and the authority or institution that issued it. The proposed amendment to Permenkumham No. 6 of 2023 aims to delegate the authority to affix signatures on Notarus documents used abroad to notaries.